Analysis of MRSA Staphylococcal Chromosome cassette mecA status from next generation sequence data - Goulden, Matthew G (Cranfield University, 2012)
NGS sequencing libraries prepared on an Illumina NGS platform for 10 isolates of Staphylococcus aureus were analysed. After extensive pre-processing to address library quality issues, for each isolate the status of the Staphylococcal Chromosome Cassette, and its mecA gene specifying resistance to meticillin, was determined. All mecA-positive isolates encoded canonical mecA. None encoded the new variant mecA identified in strain LGA251.
Keywords: core genome; accessory genome; NGS sequencing libraries; drug resistance